Additive Manufacturing through Galvanoforming of 3D Nickel Microarchitectures: Simulation‐Assisted Synthesis. Issue 12 (6th September 2018) - Schürch, Patrik; Pethö, Laszlo; Schwiedrzik, Jakob; Michler, Johann; Philippe, Laetitia
Abstract: Electrodeposition in combination with templates created by two‐photon lithography is used to fabricate dense metallic 3D microcomponents. Nanocrystalline nickel microcomponents deposited from nickel sulfamate electrolyte in 3D templates are presented. Using 3D electrodeposition simulation, different template designs for a bridge‐like microcomponent are investigated. The influence of the template design on current density is described. Electrodeposition conditions and pulse parameters are optimized with the simulation to achieve a high filling ratio within the template. Unlike previous work done in the field, the templates are made from negative tone photoresist, which is removed subsequent to the electrodeposition with plasma etching process. This allows for free‐form galvanoforming of freestanding nanocrystalline nickel microcomponents. Focused ion beam cross sections are made to investigate the microstructure within the specimen. The grains within the specimen show elongation along growth direction. Furthermore, the grain size distribution within the specimen shows correlation to the local current density values supplied by the simulation. Abstract : Nanocrystalline 3D microcomponents are created by pulse‐reverse electrodeposition into a template made by two‐photon lithography. Electrodeposition simulation is used to investigate differences in template design and to determine the influence of the reverse pulse electrodeposition. Subsequent analysis of the microstructure reveals nanocrystalline microstructure with larger grains correlating to lower local current density values shown by the simulation.